Electrochemical fluorescence switching from a patternable poly(1,3,4-oxadiazole) thin film - Seo, Seogjae; Kim, Yuna; You, Jungmok; Sarwade, Bhimrao D.; Wadgaonkar, Prakash P.; Menon, Shamal K.; More, Arvind S.; Kim, Eunkyoung (Macromolecular Rapid Communications, 2011)
A highly soluble poly(1,3,4-oxadiazole) (POD) substituted with long alkyl chains was examined for electrochemical fluorescence switching. The high solubility of the polymers enabled a simple fabrication of an electrochemical cell, which showed reversible fluorescence switching between dark (n-doping) and bright (neutral) states with a maximum on/off ratio of 2.5 and a cyclability longer than 1000 cycles. Photochemical cleavage of the oxadiazole in POD allowed photo-patterning of the POD film upon exposure to UV source. The patterned POD films displayed patterned image reversibly under a step potential of +1.8/-1.8V.
Keywords: fluorescence; lithography; Luminescence; photochemistry; switching device

Green synthesis of silver nanoparticles using sunlight - Bhaduri, Gaurav A.; Little, Ross; Khomane, Ramdas B.; Lokhande, Suhas U.; Kulkarni, Bhaskar D.; Mendis, Budhika G.; Siller, Lidija (Journal of Photochemistry and Photobiology A-Chemistry, 2013)
Silver nanoparticles (AgNPs) are currently among the most widely used man-made nanomaterials, present in a huge range of consumer products. Here we report a simple `green' method of AgNP synthesis of using an anionic surfactant without use of any additional reducing agents. It was observed that synthesis of AgNPs at room temperature (25-35 degrees C) using sodium dodecyl sulphate (SDS) and sunlight. The nanoparticles have been characterised using high-resolution transmission electron spectroscopy (HRTEM), UV-vis spectrophotometry, X-ray photoelectron spectroscopy (XPS) and Fourier Transform Infrared Spectroscopy (FTIR) and are found to have an average diameter of 30 nm. The nanoparticles are water soluble and the nature of the process is amenable to scaling up. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: photochemistry; silver nanoparticles; Sodium dodecyl sulphate; XPS

Disordered mesoporous TiO2-xNx+Nano-Au: an electronically integrated nanocomposite for solar H-2 generation - Sivaranjani, Kumarsrinivasan; Rajaambal, Sivaraman; Das, Tanmay; Roy, Kanak; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
We report on H-2 generation by photocatalysis driven by simulated white light by electronically integrated Au nanoparticles with multifunctional, disordered mesoporous TiO2-xNx (Au-NT) nanocomposites. Solar H-2 generation (1.5 mmolh(-1)g(-1)) from aqueous methanol has been demonstrated with Au-NT nanocomposites. The water splitting activity of Au-NT is attributed to the 21.1 ps lifetime of charge carriers observed from fluorescence lifetime measurements, which indicates a high electron-injection efficiency from nano-Au to the conduction band of TiO2, and hence charge separation as well as utilization. This is directly supported by the observation of a high photoluminescence emission intensity with Au-NT that highlights the energy transfer from nano-Au to TiO2. The p-n heterojunction observed between the Au (001) and TiO2 (101) facets helps to-wards the higher charge separation and their utilization. A low mesochannel depth (< 10 nm) associated with disordered mesoporous TiO2-xNx helps the charge carriers to move towards the surface for redox reactions and hence charge utilization. Visible-light absorption, as a result of the surface plasmon resonance of nano-Au, is observed in a broad range between 500 and 750 nm, which helps in harvesting visible-light photons. Finally, electronically integrated nano-Au with TiO2-xNx in Au-NT is evident from Raman and X-ray photoelectron spectroscopy measurements. All of these factors help to achieve a high rate of H-2 production. It is likely that a higher rate of H-2 production than that reported here is feasible by strategically locating Au clusters in porous TiO2 to generate hot spots through electronic integration.
Keywords: heterogeneous catalysis; Hydrogen; mesoporous materials; photochemistry; water splitting